2010
DOI: 10.1063/1.3475433
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced fluorescence measurements of the cylindrical Hall thruster plume

Abstract: An investigation of a fully cylindrical Hall thruster was performed using laser induced fluorescence (LIF) to measure ion velocity profiles in the plume. The measurements confirm a previously reported 9% increase in the exhaust energy when the cathode keeper draws an excess current (overrun mode). Furthermore, the velocity directions in the plume remain relatively unchanged for the cusped and direct magnetic field configuration in both overrun and nonoverrun modes. Previously reported plume narrowing in the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…This is different from all electromagnet versions of the CHT, in which high energy ions are 13 accelerated towards and parallel to the thruster centerline. 21 . It is hypothesized that this difference in the ion acceleration between the cylindrical thrusters with electromagnet coils and permanent magnets is, in large part, because of a stronger axial magnetic field outside the permanent magnet thrusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is different from all electromagnet versions of the CHT, in which high energy ions are 13 accelerated towards and parallel to the thruster centerline. 21 . It is hypothesized that this difference in the ion acceleration between the cylindrical thrusters with electromagnet coils and permanent magnets is, in large part, because of a stronger axial magnetic field outside the permanent magnet thrusters.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, recent laser induced fluorescence measurements of the CHT with electromagnets revealed that magnetic field surfaces outside this thruster are not equipotential. 21 Keeping in mind that the outside magnetic field topology in the CHT thrusters is very different, the applicability of these results obtained for electromagnet thrusters to the permanent magnet thruster is not so obvious. Although the paraxial approximation does not seem to be applicable to complex magnetic field topologies of the CHT thrusters, focusing and defocusing regions likely exist in these thrusters as well.…”
mentioning
confidence: 99%
“…This regime was usually achieved at the keeper current of larger than 1 A. 2,4,12,13,14 In the experiments with electromagnet CHT, the cathode placement with the respect to the thruster was fixed. The cathode outlet orifice was located approximately 5.4 cm away radially and 2.0 cm downstream from the center of the channel exit.…”
Section: Thruster Design and Experimental Setupmentioning
confidence: 99%
“…1 and 2. For the CHTem thrusters, the cathode placement was different: the cathode outlet orifice was located approximately 5.4 cm away radially and 2 cm downstream from the center of the channel exit 14.…”
mentioning
confidence: 99%
“…Spectroscopic techniques like optical emission spectroscopy [3], laser absorption spectroscopy [4], and laser-induced fluorescence [5] are also applied, but less frequently. Recently, force measurements were performed in the beam of an industrial broad-beam ion source that is very similar to the plume of gridded ion thrusters [6].…”
Section: Introductionmentioning
confidence: 99%